The future of international development cooperation : fragmentation, adaptation and innovation in a changing world - Silva, Ana Luísa; Bernardo, Luís Pais; Mah, L. (2021)
This study stemmed from the need perceived by the Portuguese Platform of NGDOs (PPNGDO) to produce knowledge that will help its members carry out a more informed analysis of the changes in International development cooperation (hereafter, development cooperation). Understanding the transformation underway and the challenges it presents is fundamental for the PPNGDO and its members to jointly outline possible paths into the future, setting out the future direction of action, their priorities and their options. The study was conducted with three goals in mind: 1) tracing the progress of development cooperation over the past 20 years, while reflecting and discussing the ongoing changes in a multiplex world; 2) addressing the challenges faced by key public and private development cooperation actors view of the ongoing change; 3) contributing to the discussion on this new configuration of development cooperation by offering guidelines based on adaptation and innovation for thinking and acting in a complex, fragmented and fragile multiplex world. This study sought to review the available academic and grey literature (reports from development cooperation organisations, blog posts, online discussions and interviews), and where possible, interviews with professionals from international organisations – both governmental and non-governmental – were used. In the introduction of the study, we contextualise development cooperation in a changing world and describe the framework for discussion applied to each of the following sections: In Part I, changes in development cooperation and ODA are addressed, based on three issues that are crucial for the sectors: quantity, quality and legitimacy. Part II highlights the challenges faced by key public and private actors of development cooperation - either ‘“traditional’” or ‘“new’” ones. Finally, Part III outlines a few guidelines on complexity, fragmentation, and fragility, which can provide useful tools for analysis in the new context. To conclude, we offer civil society organisations some points for reflection.